Association between Blood Sugar, Methyl-paraben, and Albumin Concentrations in Women with Hyperglycemic: Hubungan antara Gula Darah, Metil-paraben, dan Konsentrasi Albumin pada Wanita dengan Hiperglikemik - Jesas, Lamiah Mohseen Alivi; Hayati, Nasim; Davoodi, Fatemeh (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Type 2 diabetes is a type of metabolic disorder, and the role of parabens as endocrine-disrupting chemicals in the physiological process of diabetes and their effects on the function of serum albumin has always been a scientific paradox. Until now, there is little information about the correlation between parabens and sugar level of diabetic people as well as their effect on albumin concentration in Iranian society, which has been investigated as the most important objective of this research. Aim of Study: The study aimed to investigation the relationship between blood sugar, methyl-paraben, and albumin diabetic Women. Material and Method: 200 diabetic patients and 75 control were subjected to laboratory tests. Demographic data were prepared and analyzed. The concentration of methyl paraben and albumin were statistically analyzed. The results: The demographic data showed that there is a significant relationship between the diabetic group and the control in the age factor and body mass index (P=0.012). The analysis of laboratory data showed that there was no significant relationship between blood sugar concentration and albumin (P=0.577) and between blood sugar concentration and methyl paraben concentration (P=0.532). Furthermore, the statistical test showed that there was no significant relationship between the concentration of albumin and the concentration of methyl paraben (P=0.374). Conclusion: The results of this research show that there is no statistical relationship between the concentrations of FBS, methyl paraben and albumin, which can be the result of genetic diversity in the Iranian diabetic community with other populations in different parts of the world. Highlights: No significant correlation was found between blood sugar, methyl paraben, and albumin levels in Iranian diabetic women. Demographic factors such as age and body mass index showed a significant association with diabetes risk. Statistical tests confirmed non-normal data distribution and absence of meaningful correlations among the three studied biomarkers. Keywords: Type 2 Diabetes, Methyl Paraben, Albumin, Iranian Women, Blood Sugar